Interventions to improve screening and appropriate referral of patients with cancer for distress: systematic review protocol. Issue 9 (21st September 2015) - McCarter, Kristen; Britton, Ben; Baker, Amanda; Halpin, Sean; Beck, Alison; Carter, Gregory; Wratten, Chris; Bauer, Judy; Booth, Debbie; Forbes, Erin; Wolfenden, Luke
Abstract : Introduction: It is estimated that 35–40% of patients with cancer experience distress at some stage during their illness. Distress may affect functioning, capacity to cope, treatment compliance, quality of life and survival of patients with cancer. Best practice clinical guidelines recommend routine psychosocial distress screening and referral for further assessment and/or psychosocial support for patients with cancer. However, evidence suggests this care is not provided consistently. Methods and analysis: We developed our methods following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement. The review is registered with PROSPERO and any amendments to the protocol will be tracked. The primary aim of this systematic review is to examine the impact of interventions delivered in healthcare settings that are aimed at (1) improving routine screening of patients for psychosocial distress and (2) referral of distressed patients with cancer for further assessment and/or psychosocial support. The effectiveness of such interventions in reducing psychosocial distress, and any unintended adverse effect of the intervention will also be assessed in patients with cancer. Data sources will include the bibliographic databases Cochrane Central Register of Controlled trials (CENTRAL) in the Cochrane Library, MEDLINE, EMBASE, PsycINFO and CINAHL. Eligible studies must compare an intervention (or two or more interventions) in a healthcare setting to improve the rate of screening for psychosocial distress and/or referral for further assessment and/or psychosocial support for patients with cancer with no intervention or 'usual' practice. Two investigators will independently review titles and abstracts, followed by full article reviews and data extraction. Disagreements will be resolved by consensus and if necessary, a third reviewer. Where studies are sufficiently homogenous, trial data will be pooled and meta-analyses performed. Ethics and dissemination: No ethical issues are foreseen. The findings of this study will be disseminated widely via peer-reviewed publications and conference presentations. Systematic review registration: PROSPERO registration number CRD4 2015017518.